Chemoradiotherapy in limited-disease small-cell lung cancer. (August 2012) - Fukuda, Minoru; Ogawara, Daiki; Nakamura, Yoichi; Kohno, Shigeru
SUMMARY Systemic chemotherapy is the mainstay of treatment for small-cell lung cancer. A third of small-cell lung cancer patients present with limited disease; in this population, thoracic radiotherapy caused a 14% reduction in the mortality rate, and benefit in terms of overall survival at 3 years was 5.4% as compared with chemotherapy alone. Although the optimal schedule and volume of thoracic radiotherapy remain controversial, early twice-daily concurrent radiotherapy with etoposide plus cisplatin is recommended. Prophylactic cranial irradiation is recommended for patients with any response to first-line treatment. Maintenance and dose-intense treatment is not recommended outside of clinical trials. Large randomized trials that compare standard-dose radiation therapy of 45 Gy in twice-daily fractions for 3 weeks with once-daily schedules with a higher total dose are ongoing. The incorporation of new drugs is warranted for future combined modality treatment.